A recurrence analysis in patients with congenital choanal atresia - Yılmaz Topçuoğlu, Miray-Su; Schuler, Patrick; Westhoff, Jens; Sommerburg, Olaf; Baumann, Ingo (Journal of cranio-maxillofacial surgery, 2025)
Recurrences following congenital choanal atresia (CA) repair are a particular challenge. This study sought to investigate the underlying causes of recurrences. The study compared 33 primary surgeries (controls, median age 32 months) to 34 revision surgeries (revision group, median age 10 months) performed between 2010 and 2024 at the department of otorhinolaryngology of a German university hospital. Demographic data, surgery time [min], length of hospitalization [nights] and the intraoperatively identified causes of recurrences were analysed. To test for differences between the two groups, the Mann-Whitney-U test was applied. The Chi-square test was used to test for correlations. In the revision group, 88 % (30/34) of the recurrences were attributable to insufficient vomer resections. An additional 12 % (4/34) were attributable to granulations. The revision group was more likely to have a bilateral choanal atresia (p < 0.001). Surgery time was equal in both groups (p = 0.115). Dominantly, insufficient posterior vomer resections, but also granulation tissue growth present the primary causes of recurrence. Adequate resection of the posterior vomer is essential for optimal outcomes and can be achieved with small effort. The implementation of this technique as standard procedure has the potential to reduce the risk of recurrence and enhance the care of patients with CA.
Gesehen am 16.01.2026